Patient factors associated with increased acute care costs of hip fractures: a detailed analysis of 402 patients. Issue 1 (December 2016) - Aigner, R.; Meier Fedeler, T.; Eschbach, D.; Hack, J.; Bliemel, C.; Ruchholtz, S.; Bücking, B.
Abstract Summary The aim of the present study was to identify patient factors associated with higher costs in hip fracture patients. The mean costs of a prospectively observed sample of 402 patients were 8853 €. The ASA score, Charlson comorbidity index, and fracture location were associated with increased costs. Purpose Fractures of the proximal end of the femur (hip fractures) are of increasing incidence due to demographic changes. Relevant co-morbidities often present in these patients cause high complication rates and prolonged hospital stays, thus leading to high costs of acute care. The aim of this study was to perform a precise cost analysis of the actual hospital costs of hip fractures and to identify patient factors associated with increased costs. Methods The basis of this analysis was a prospectively observed single-center trial, which included 402 patients with fractures of the proximal end of the femur. All potential cost factors were recorded as accurately as possible for each of the 402 patients individually, and statistical analysis was performed to identify associations between pre-existing patient factors and acute care costs. Results The mean total acute care costs per patient were 8853 ± 5676 € with ward costs (5828 ± 4294 €) and costs for surgical treatment (1972 ± 956 €) representing the major cost factors. The ASA score, Charlson comorbidity index, and fracture location were identified as influencing the costs of acute care for hip fracture treatment. Conclusion Hip fractures are associated with high acute care costs. This study underlines the necessity of sophisticated risk-adjusted payment models based on specific patient factors. Economic aspects should be an integral part of future hip fracture research due to limited health care resources.